Peran Guru Ekstrakurikuler dalam Mengembangkan Bakat Siswa di MI Miftahul Ulum 02 Gumukrejo Karangsono Bangsalsari Jember - Ni’mah Lailatul Mas’adah; Ali Murtadlo (Bidayatuna, 2019)
One of the roles of teachers in developing children's talents is helping the child from the side of independence, guiding and encouraging talents and aspects of social personality, especially in developing motor skills through planning guidance and providing adequate supporting facilities. Activities that are interesting in this development are through extracurricular activities, such as Qiroah, speech, and Calligraphy. This research is focused on the role of extracurricular teachers in developing children's talents at MI Miftahul Ulum 02 Gumukrejo Karangsono Bangsalsari Jember which focuses on supporting and inhibiting factors. This study uses a qualitative approach with case study research. The role of extracurricular teachers in developing children's talents is raising several indicators of success through extracurricular activities that extracurricular teachers concern and always strive for, namely Qiroah, speech and calligraphy; supported by a) The teachers having high enthusiasm and profesionalism; b) The existence of adequate infrastructure; c) The enthusiasm of the teachers in cooperating extracurricular activities; while the obstacle is that students only participate in activities without any response, such as when doing qiroah activities they just follow, they have no enthusiasm to show their abilities.